Multigenerational effects of bisphenol A or ethinyl estradiol exposure on F2 California mice (Peromyscus californicus) pup vocalizations. - Sarah A Johnson; Michelle J Farrington; Claire R Murphy; Paul D Caldo; Leif A McAllister; Sarabjit Kaur; Catherine Chun; Madison T Ortega; Brittney L Marshall; Frauke Hoffmann; Mark R Ellersieck; A Katrin Schenk; et al. (PLoS ONE)
Rodent pups use vocalizations to communicate with one or both parents in biparental species, such as California mice (Peromyscus californicus). Previous studies have shown California mice developmentally exposed to endocrine disrupting chemicals, bisphenol A (BPA) or ethinyl estradiol (EE), demonstrate later compromised parental behaviors. Reductions in F1 parental behaviors might also be due to decreased emissions of F2 pup vocalizations. Thus, vocalizations of F2 male and female California mice pups born to F1 parents developmentally exposed to BPA, EE, or controls were examined. Postnatal days (PND) 2-4 were considered early postnatal period, PND 7 and 14 were defined as mid-postnatal period, and PND 21 and 28 were classified as late postnatal period. EE pups showed increased latency to emit the first syllable compared to controls. BPA female pups had decreased syllable duration compared to control and EE female pups during the early postnatal period but enhanced responses compared to controls at late postnatal period; whereas, male BPA and EE pups showed greater syllable duration compared to controls during early postnatal period. In mid-postnatal period, F2 BPA and EE pups emitted greater number of phrases than F2 control pups. Results indicate aspects of vocalizations were disrupted in F2 pups born to F1 parents developmentally exposed to BPA or EE, but their responses were not always identical, suggesting BPA might not activate estrogen receptors to the same extent as EE. Changes in vocalization patterns by F2 pups may be due to multigenerational exposure to BPA or EE and/or reduced parental care received.